The Correlation between Vocabulary Learning Strategies and Vocabulary Mastery - Nurhayati, Nurhayati; Lolong, Chikita (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to determine the correlation between vocabulary learning strategies and vocabulary mastery. A questionnaire was distributed to students of class VIII A, B, C and D of SMP Advent Airmadidi to determine the level of use of vocabulary learning strategies and vocabulary mastery. To answer the research questions, descriptive mean analysis and Pearson Correlation Coefficient Correlation were used to answer the research questions. The research findings revealed that: (1) the level of students' vocabulary learning strategies was 3.41, indicating a moderate level; (2) the level of students' vocabulary mastery was 82.44 indicating good vocabulary mastery; and (3) the p value = 0.781, and r = 0.028, indicating that there was no significant correlation between vocabulary learning strategies and vocabulary mastery. The interpretation of the research findings shows that although there is no significant correlation between vocabulary learning strategies and vocabulary mastery, the use of various vocabulary learning strategies still contributes positively to students' vocabulary mastery. Therefore, teachers can expand the vocabulary learning strategies they use in the classroom, as well as provide more focused support to students in choosing and applying strategies that suit their individual learning strategies